Aerobic physical exercise modifies the prostate tumoral environment - Veras, Allice Santos Cruz [UNESP]; Correia, Rafael Ribeiro [UNESP]; Batista, Victor Rogério Garcia [UNESP]; Tavares, Maria Eduarda de Almeida [UNESP]; Rubira, Rafael Jesus Gonçalves [UNESP]; Fiais, Gabriela Alice [UNESP]; Giometti, Inês Cristina; Chaves-Neto, Antonio Hernandes [UNESP]; Teixeira, Giovana Rampazzo [UNESP] (Elsevier, 2023)
Exercise is recognized for its potential role in reducing the risk of certain cancers. However, the molecular mechanisms behind this risk reduction are not fully understood. Here, we hypothesized that aerobic physical exercise induces cancer attenuating effects through the modulation of oxidative stress and inflammation. To test this hypothesis, twenty male Sprague Dawley rats with chemically induced prostate tumors were divided into two groups: Prostate cancer (PC) in the absence and presence of exercise (PC + Ex). Rats in the PC + Ex group performed exercises on a treadmill for 8 weeks, 5 sessions per week, at an intensity of 60 % of maximum capacity. Weight and feed efficiency, Ki-67, apoptosis, prostatic inflammation, and markers of oxidative stress were analyzed. We found that aerobic physical exercise significantly decreased prostate cell proliferation (p < 0.05) across modulation, tumor size, and prostate weight. The PC + Ex group also significantly reduced anti-apoptosis protein expression (p < 0.05) and increased pro-apoptotic protein expression. Furthermore, physical exercise increased enzymatic antioxidant defenses in the prostate, plasma, and whole blood. Moreover, PC + Ex reduced lipid peroxidation and protein carbonyl levels (p < 0.05). In the prostate, there was an increase in anti-inflammatory cytokines (IL-10), and a reduction in pro-inflammatory cytokines (IL-6, TNF-α, and NF-κB) after 8 weeks of physical exercise. In conclusion, we found that aerobic physical exercise is a functional, beneficial, and applicable approach to control PC progression, because it modifies the systemic environment, including the regulation of glucose and circulating lipids. This modification of the cancer cells environment has anti-inflammatory and antioxidant effects that attenuate tumor growth.
Keywords: AR; Endurance physical training; Feed efficiency; Raman spectroscopy; Redox state